Conversion of glucose into 5-hydroxymethylfurfural with boric acid in molten mixtures of choline salts and carboxylic acids. (January 2015) - Matsumiya, Hiroaki; Hara, Takeyoshi
Abstract: The conversion of glucose into a potential platform chemical for fuels and plastics, 5-hydroxymethylfurfural (HMF), has been studied using B(OH)3 as a promoter in different solvents, namely molten mixtures made of choline salts and carboxylic acids, with the aim of developing an inexpensive and less harmful alternative to Cr/ionic liquid systems. Choline chloride-based molten mixtures afforded poor yields of HMF, whereas the yields were improved by replacing choline chloride with choline dihydrogen citrate. The combination of choline dihydrogen citrate and glycolic acid was the best choice, providing an HMF yield of ∼60% at 140 °C within 4 h by adding a small volume of water as a co-solvent. Graphical abstract: Highlights: Mixtures of choline salts and carboxylic acids were melted at room temperatures. The molten mixtures served as solvents for the B(OH)3 -promoted formation of HMF. The combination of choline dihydrogen citrate and glycolic acid was the best choice. The addition of small volumes of water as a co-solvent improved the HMF yield.